Why Would Anyone Do That? : Lifestyle Sport in the Twenty-First Century - Poulson, Stephen C., 1966- (Book collections on Project MUSE., 2016)
Focusing largely on triathlon and "extreme" mountain biking, sociologist Stephen C. Poulson offers a fascinating exploration of the new lifestyle sports, shedding light on why people find them so compelling. Drawing on interviews with competitors, on his own experience as a participant, and other materials, Poulson looks at the commodification of the new sports, the types of people who decide to participate, those most often excluded, and whether or not participation in lifestyle sport should always be considered "good" for athletes.